Tari Wayang Karakter Satria Ladak - Sumiati, Lilis (PANGGUNG, 2012)
Wayang dance is a dance expressing events in the stories of wayang. The events here among oth- ers are dances revealing the background of the story, theme, the name of the dance, characters, and philosophical elements. Of those various elements, the scope in this study is limited into matters of satria ladak character.Wayang dance satria ladak character living in several areas contains some significant differences in several aspects. The term differing the specialty of wayang dance is called sejak. The scope of se- jak is more for oneÃ¢â¬â¢s style in dancing dance genre from the same ethnic. Therefore, the term sejak is firstly come out when seeing oneÃ¢â¬â¢s performance in dancing, either referred to her/his choreography or to her/his specialty in performing the dance. Then, sejak owned by the individual is spread among his/her surrounding, so that it can be an icon in respective areas.The quantity of Wayang dance satria ladak is varied in each areas, such as sejak Sumedang is Dipati Karna dance. While Sejak Garut is Bambang Somantri dance, and sejak Bandung is Arayana dance. These materials are chosen as samples for comparative and interpretative study.Keywords: Wayang Dance, Satria Ladak, Sejak, comparative, interpretative.ÃÂ ÃÂ